The Influence of Grocery Branding and Excellent Service on the Success of UD Aulia Gunung Raya Grocery Store, Bilah Barat District, Labuhanbatu Regency - Deswita Mayrani Pasaribu; Jeni Sukmal; Shopiah Anggraini Rambe (International Journal of Economics and Management Research, 2025)
The aim of this research is to determine whether or not basic food branding and excellent service have a significant influence on the success of the UD Aulia Gunung Raya basic food shop, Barbar Barat subdistrict, Labuhanbatu regency. The research uses quantitative methods and an associative causality approach. The data collection technique used is through observation and interviews. The sample in this research was 88 respondents or consumers. The sampling technique is simple random sampling. The data analysis technique uses statistical techniques/SPSS by carrying out validity and reliability tests then for questionnaires and multiple linear regression analysis with T Test and F Test to prove the hypothesis. The research results show that there is a close and significant influence of basic food branding on store success, there is a close and significant influence of excellent service on store success. The influence of basic food branding and excellent service is 97.6% and the remaining 2.3% is influenced by other factors and variables.